NOTES ON BOTHRIOCHLOA KUNTZE (GRAMINEAE: ANDROPOGONEAE) IN MALESIA - Alex Sumadijaya; Jan Frits Veldkamp (Research Center for Biology, 2009)
SUMADIJAYA, A. & VELDKAMP, J.F. 2009. Notes on Bothriochloa Kuntze (Gramineae: Andropogoneae) in Malesia. Reinwardtia 12(5): 415 – 417. — The note is preliminary part for studies of Bothriochloa Kuntze in Malesia. Special caution should be given to Bothriochloa intermedia (R. Br.) A. Camus, now B. bladhii (Retz.) S.T. Blake, because of the variation, synonyms, and natural hybridization to generic level.